Bend it like Beckham or fix them like Florence—proportional representation of healthcare in New Year honours: an observational study. (18th December 2019) - Emelifeonwu, John A; Hazelwood, James E; Nolan, Oscar; Sharland, Emma; O'Donald, Anna; Peet, Alison; Frazer, Ricky
Abstract: Objectives: To compare the proportional representation of healthcare workers in receipt of New Year honours (NYHs) with workers in other industries and to determine whether the NYH system has gender or geographical biases. Design: Observational study of the UK honours system with a comparative analysis of proportional representation of the UK workforce and subgroup analyses of gender and geographical representations. Participants: Recipients of NYHs from 2009 to 2018. Main outcome measures: Absolute risk of receiving an NYH based on industry, gender, or region of the UK. Relative risk of receiving an NYH for services to healthcare compared with other industries. Results: 10 989 NYHs were bestowed from 2009 to 2018, 47% of which were awarded to women. 832 awards (7.6%) were for services to healthcare. People working in sport and in the arts and media were more likely to receive NYHs than those working in healthcare (relative risks of 22.01 (95% confidence interval 19.91 to 24.34) and 5.84 (5.31 to 6.44), respectively). There was no significant difference between the rate of receiving honours for healthcare and for science and technology (P=0.22). 34% (3741) of awards were issued to people living in London and in the southeast of England, and only 496 of 1447 (34%) higher order awards (knighthoods, damehoods, companions of honour, and commanders of the order of the British empire) were received by women. Conclusions: In relation to the size of its workforce, a career in healthcare is not as "honourable" as careers in certain other industries. Geographical and gender biases might exist in the honours system.